Gradnja uporabniškega vmesnika na temelju programskega paketa MATLAB za študij sistemov - Leš, Martina (Strojniški vestnik, 2002)
Software technology provides a highly interactive and powerful learning environment for system theory and simulation in some engineering disciplines. This paper describes the development and implementation of an educational tool for linear systems theory that connects electronic manuscripts with examples in Matlab and Simulink through a graphical user interface for versions 5 and 6 of Matlab. This is a graphical application that offers undergraduate students additional support by presenting linear systems theory in their native language. It provides students with a foundation for independent studies and distance learning. The main focus in this paper is given to the graphical interface structure, which is ilustrated with an example. We conclude the paper with an analysis of different computer-assisted learning methods.
Keywords: teorija linearnih sistemov; Matlab; orodja učna; vmesniki grafični; vmesniki uporabniški; učenje; learning; računalniški program Matlab; linearni sistemi